2017
DOI: 10.1089/gtmb.2016.0284
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between MGMT Promoter Methylation and Patients with Gastric Cancer: A Meta-Analysis

Abstract: Our findings provide evidence that MGMT promoter methylation could play an important role in gastric carcinogenesis and may serve as an important biomarker for gastric cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…On the correlation of methylation with overall survival, 3-OS and 5-OS were significantly lower in patients harbouring MGMT methylation compared to negative ones. Loss of MGMT expression has a significant impact on various types of cancers, mainly colorectal cancer [16,[24][25][26]. Hence, Ahmed et al noted that MGMT expression was significantly correlated with tumor stage and metastatic status [16].…”
Section: Discussionmentioning
confidence: 99%
“…On the correlation of methylation with overall survival, 3-OS and 5-OS were significantly lower in patients harbouring MGMT methylation compared to negative ones. Loss of MGMT expression has a significant impact on various types of cancers, mainly colorectal cancer [16,[24][25][26]. Hence, Ahmed et al noted that MGMT expression was significantly correlated with tumor stage and metastatic status [16].…”
Section: Discussionmentioning
confidence: 99%
“…MGMT promoter methylation is also associated with the occurrence and invasion of melanoma [9]. Furthermore, MGMT methylation can also be used as a biomarker to predict carcinogenesis in a variety of tumors [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…So far, several methylation biomarkers have been reported in GC. For example, a meta‐analysis of 14 studies showed that MGMT promoter methylation could play an important role in gastric carcinogenesis (Yuan et al, ). Furthermore, DNA hypermethylation of several tumor‐suppressor genes such as CDH1 , CDKN2A , MLH1 , RUNX3 , and EIF4E was associated with gastric carcinogenesis (Ge et al, ; Hu, Qin, Zhang, Ye, & Huang, ).…”
Section: Introductionmentioning
confidence: 99%